Public spaces and neoliberal policies: The Greek case - Despina Dimelli (PlaNext)
The process of neoliberalizing public spaces involves implementing policies aimed at increasing capital flow to offset reductions in local budgets. In Greece, although public spaces are decisive elements of the urban tissue, the tools, strategies, and mechanisms for their development are mainly based on public funding and the role of the private sector is still weak. The current paper analyzes the policies for public spaces since 1950 until today and the role of public and private sectors in their development. It focuses on specific periods as the Olympic Games, the economic crisis and today, to investigate the policies followed for public spaces development. The research area is the capital of Greece, and the examined case studies include both small- and large-scale areas to cover different types of public spaces. Research focuses on the changes in the legislative framework to promote the role of private sector and evaluates its role and collaboration with the public sector. The analysis of the case studies shows that constrained expertise, centralized decision-making procedures, and inadequate coordination of synergies among management entities, have resulted in notable deficiencies in the partnerships between the public and private sectors in supporting projects for the regeneration of public areas.